Studi Perencanaan Pipa Penstock Pada Pembangunan PLTA Poso - Alhabsyi, Alawiyah Chaerunisa; Badrun, Burhanuddin; Yusuf, Andi Rumpang (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Development of water through the construction of dams where development has a goal to improve the quality of all aspects of people's lives, namely social, cultural and economic aspects in order to realize social welfare. The implementation of a dam construction project that requires more expertise to complete the final work, always requires a project completion time and that has been specified in the work contract. The active role of management is one of the main keys to the success of project management in achieving targets in terms of cost, quality and time. In the construction of this dam requires an implementation method which includes: preparatory work (land clearing and stripping, mobilization, work roads, making board directors, and project nameplates, building facilities and infrastructure for office buildings, workshop warehouses, and providing clean water and lighting, and connecting roads from the highway to the project site.), construction of evasion channels, excavation of soil and used to make upstream and downstream cofferdams. The Poso River that flows from Lake Poso to generate electricity With an average discharge of 148 m3 per second, its energy potential is enormous. PT Poso Energy has 3 concessions for hydroelectric power plants on the river with a total of 600 MW